Expression of a Diverse Array of Ca2+-Activated K+ Channels (SK1/3, IK1, BK) that Functionally Couple to the Mechanosensitive TRPV4 Channel in the Collecting Duct System of Kidney - Li, Yue; Hu, Hongxiang; Butterworth, Michael B.; Tian, Jin-Bin; Zhu, Michael X.; O’Neil, Roger G. (PLOS ONE, 2016)
The voltage- and Ca2+-activated, large conductance K+ channel (BK, maxi-K) is expressed in the collecting duct system of kidney where it underlies flow- and Ca2+-dependent K+ excretion. To determine if other Ca2+-activated K+ channels (KCa) may participate in this process, mouse kidney and the K+-secreting mouse cortical collecting duct (CCD) cell line, mCCDcl1, were assessed for TRPV4 and KCa channel expression and cross-talk. qPCR mRNA analysis and immunocytochemical staining demonstrated TRPV4 and KCa expression in mCCDcl1 cells and kidney connecting tubule (CNT) and CCD. Three subfamilies of KCa channels were revealed: the high Ca2+-binding affinity small-conductance SK channels, SK1and SK3, the intermediate conductance channel, IK1, and the low Ca2+-binding affinity, BK channel (BKα subunit). Apparent expression levels varied in CNT/CCD where analysis of CCD principal cells (PC) and intercalated cells (IC) demonstrated differential staining: SK1:PC<IC, and SK3:PC>IC, IK1:PC>IC, BKα:PC = IC, and TRPV4:PC>IC. Patch clamp analysis and fluorescence Ca2+ imaging of mCCDcl1 cells demonstrated potent TRPV4-mediated Ca2+ entry and strong functional cross-talk between TRPV4 and KCa channels. TRPV4-mediated Ca2+ influx activated each KCa channel, as evidenced by selective inhibition of KCa channels, with each active KCa channel enhancing Ca2+ entry (due to membrane hyperpolarization). Transepithelial electrical resistance (TEER) analysis of confluent mCCDcl1 cells grown on permeable supports further demonstrated this cross-talk where TRPV4 activation induce a decrease in TEER which was partially restored upon selective inhibition of each KCa channel. It is concluded that SK1/SK3 and IK1 are highly expressed along with BKα in CNT and CCD and are closely coupled to TRPV4 activation as observed in mCCDcl1 cells. The data support a model in CNT/CCD segments where strong cross talk between TRPV4-mediated Ca2+ influx and each KCa channel leads to enhance Ca2+ entry which will support activation of the low Ca2+-binding affinity BK channel to promote BK-mediated K+ secretion.